Pengaruh Pemberian Kuis Awal Pertemuan Melalui Model Pembelajaran Pencapaian Konsep terhadap Motivasi dan Hasil Belajar Siswa Kelas X SMA Negeri 1 Liliriaja (Studi pada Materi Ikatan Kimia) - Nova Wulandari Latif; Muharram Muharram; Diana Eka Pratiwi (Jurusan Kimia FMIPA UNM, 2021)
This study is a quasi-experimental research aimed to determine the effect of giving quiz in the beginning of each meeting through concept attainment learning toward the motivation and student achievement on class X SMAN 1 Liliriaja. The independent variable in this study is using quiz in the beginning of each meeting through the concept attainment learning on the experimental class and without quiz in control class, and the dependent variable is the motivation and students achievement on chemical bonding subject matter. The population was all of class X SMAN 1 Liliriaja which consists of 11 classes, and the sample consisted of two classes such as class X.1 as an experiment class with 35 students and X.2 as a control class with 35 students. The data was obtained by giving a statement motivation questioner consisting of 25 statements. Data were analyzed using a likert scale scoring and obtained by the students motivation in good category, then by using SPSS and found that the correlation between the variables has a significant correlation. Data were obtained by providing student achievement test on chemical bonding Data were obtained by providing students achievement test on chemical bonding subject matter in the form of post-test which consists of 20 items multiple choice. Data were analyzed using descriptive and inferential statistical analysis. Hypothesis testing is done by t-test products t(count) > t(table) = 4,873 > 1.67 at α ═ 0.05. T-test results prove that using quiz in the beginning of each meeting through concept attainment learning give positive effect on motivation and students achievement at class X SMA Negeri 1 Liliriaja studies on chemical bonding.